Fashioning Gender: A Case Study of the Fashion Industry - Stokes, Allyson (My University, 2013)
This dissertation uses the case of the fashion industry to explore gender inequality in creative cultural work. Data come from 63 in-depth interviews, media texts, labor market statistics, and observation at Toronto's fashion week. The three articles comprising this sandwich thesis address: (1) processes through which femininity and feminized labor are devalued; (2) the gendered distribution of symbolic capital among fashion designers; and (3) the gendered organization of the fashion industry and the “ideal creative worker.”
In chapter two, I apply devaluation theory to the fashion industry in Canada. This chapter makes two contributions to literature on the devaluation of femininity and “women's work.” First, while devaluation is typically used to explain the gender wage gap, I also address symbolic aspects of devaluation related to respect, prestige, and interpretations of worth. Second, this paper shows that processes of devaluation vary and are heavily shaped by the context in which work is performed. I address five processes of devaluation in fashion: (1) trivialization, (2) the privileging of men and masculinity, (3) the production of a smokescreen of glamour, (4) the use of free labor and “free stuff,” and (5) the construction of symbolic boundaries between “work horses” and “show ponies.”
In chapter three, I use media analysis to investigate male advantage in the predominantly female field of fashion design. I find that the “glass escalator” concept typically used to explain male advantage in feminized work, is insufficient when applied to a cultural field. The glass escalator illustrates movement upward in well-defined organizational hierarchies where success is measured by pay and promotion. But success in cultural fields is also measured by symbolic capital (celebrity, cultural consecration, prestige). I find that male designers are attributed more symbolic capital by prestigious industry sources and the fashion media. In order to illustrate these advantages I make use of the concept of a “glass runway,” whereby designers are pushed forward into the spotlight, rather than upward within a single workplace or organization. I also take note of how these advantages are structured by the intersection of gender and sexuality.
In chapter four I investigate the gendered organization of creative cultural work in the fashion industry. Literature suggests that these types of work are characterized by: (1) the need to mitigate risk through entrepreneurial labor and (2) an ideology of passion. I find that these organizing logics create a gendered conception of the “ideal creative worker.” Men more easily conform to this ideal since they have lower family responsibilities, are offered more flexible working arrangements, and since it is more culturally acceptable for men to put work before intimate life. Findings also suggest that gender intersects with age and class. The gendered organization of fashion not only reinforces inequalities between women and men, but also different groups of women. Women who are younger, childless, and have independent financial support can more easily conform to the “ideal creative worker.” Still, even women who closely match this ideal are questioned and criticized in ways that men are not.
Keywords: Sociology; Gender; Inequality; Work; Culture; Fashion; Sociology; Sociology